The effect and benefits of pet facilitated therapy (PFT) in the elderly - Zaw, Cho Cho; Ahmad, Norfadzilah; Mohd, Myat Min (Scholars Journal of Applied Medical Sciences (SJAMS), India, 2017)
With the advanced age, the elderly people are facing undergoing decline in their physical, mental and social aspects. Alzheimer, Dementia, and Cognitive function disorders are among the common health problems which has been experiencing by the elderly. Other than the conventional therapy, the complementary and alternative therapies are required to be considered for their long-term care. This study aims to identify the effects and benefits of PFT among the elderly population and their health care. The systematic literature review method is used as the research methodology. 14 articles related with the use of PFT in the elderly are chosen based on the inclusion criteria, and the findings from these studies are examined and discussed in this study. Based on the findings, it is indicated that PFT have the potential benefits on the care of the elderly with cognitive dysfunction. It is recommended to use as part of the complementary therapy in the care of older people after considering and removing the limitations. Since raising awareness about PFT and their potential benefits in the care of elderly is a necessary, it is hoped that this paper will serve as a knowledge sharing for the nurses and health care providers especially those living in areas where the use of PFT is very limited. Yet, further studies still need to be conducted in the related area to have more in-depth understanding about the application of PFT and the related matters. Keywords: Pet Facilitated Therapy (PFT), elderly people, Dementia, Alzheimer, Cognitive dysfunction